2021
DOI: 10.3390/rs13204077
|View full text |Cite
|
Sign up to set email alerts
|

On the Electron Temperature in the Topside Ionosphere as Seen by Swarm Satellites, Incoherent Scatter Radars, and the International Reference Ionosphere Model

Abstract: The global statistical median behavior of the electron temperature (Te) in the topside ionosphere was investigated through in-situ data collected by Langmuir Probes on-board the European Space Agency Swarm satellites constellation from the beginning of 2014 to the end of 2020. This is the first time that such an analysis, based on such a large time window, has been carried out globally, encompassing more than half a solar cycle, from the activity peak of 2014 to the minimum of 2020. The results show that Swarm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(30 citation statements)
references
References 64 publications
4
26
0
Order By: Relevance
“…Overall, the largest difference (∼19% after the correction) at low latitudes was noticeable for Swarm B satellite but the comparison was based on only 14-15 coincident data points. In recent work, Pignalberi et al (2021) examined and compared diurnal and seasonal variations of T e at around 510 km altitude for Jicamarca, Arecibo, and Millstone Hill ISRs using climatology obtained based on Swarm B high-gain LP data between 2014and 2020and ISR data between 1974and 2020 In their analysis of T e climatology trends, they found that the Swarm B LP T e correction given in Lomidze et al (2018) improves the agreement and noticeably reduces the overestimation, but large discrepancies remain for Jicamarca and during nighttime for Arecibo. This once again indicates a need to refine the low latitude calibration of Swarm LP T e values, and possibly incorporating latitudinal and diurnal dependence into the correction, as noted by Pignalberi et al (2021).…”
Section: Discussion and Summarymentioning
confidence: 99%
See 1 more Smart Citation
“…Overall, the largest difference (∼19% after the correction) at low latitudes was noticeable for Swarm B satellite but the comparison was based on only 14-15 coincident data points. In recent work, Pignalberi et al (2021) examined and compared diurnal and seasonal variations of T e at around 510 km altitude for Jicamarca, Arecibo, and Millstone Hill ISRs using climatology obtained based on Swarm B high-gain LP data between 2014and 2020and ISR data between 1974and 2020 In their analysis of T e climatology trends, they found that the Swarm B LP T e correction given in Lomidze et al (2018) improves the agreement and noticeably reduces the overestimation, but large discrepancies remain for Jicamarca and during nighttime for Arecibo. This once again indicates a need to refine the low latitude calibration of Swarm LP T e values, and possibly incorporating latitudinal and diurnal dependence into the correction, as noted by Pignalberi et al (2021).…”
Section: Discussion and Summarymentioning
confidence: 99%
“…In recent work, Pignalberi et al (2021) examined and compared diurnal and seasonal variations of T e at around 510 km altitude for Jicamarca, Arecibo, and Millstone Hill ISRs using climatology obtained based on Swarm B high-gain LP data between 2014and 2020and ISR data between 1974and 2020 In their analysis of T e climatology trends, they found that the Swarm B LP T e correction given in Lomidze et al (2018) improves the agreement and noticeably reduces the overestimation, but large discrepancies remain for Jicamarca and during nighttime for Arecibo. This once again indicates a need to refine the low latitude calibration of Swarm LP T e values, and possibly incorporating latitudinal and diurnal dependence into the correction, as noted by Pignalberi et al (2021). Additionally, improvements in the Swarm LP data processing and, for example, inclusion of effects associated with the presence of light ions, which can be important source of errors at low latitudes during nighttime, is recommended.…”
Section: Discussion and Summarymentioning
confidence: 99%
“…The recent statistical investigation by Pignalberi et al. (2021) examines the Swarm temperatures in terms of local time at three ISR sites. They report that the Lomidze et al.…”
Section: Resultsmentioning
confidence: 99%
“…If the cold ions gain an energy (E i ) of ∼20 eV by the EMIC waves (Figure 3f), the electron thermal energy E e is ∼0.01 eV. Since typical electron temperatures in the top-side ionosphere and in the plasmasphere are ∼0.3 eV (e.g., Comfort et al, 1985;Pignalberi et al, 2021), the estimated 0.01 eV is an unreasonable value of the electron temperature.…”
Section: Discussionmentioning
confidence: 98%